Security and VO Management Capabilities in a Large-Scale Grid Operating System - Aziz, Benjamin; Sporea, Ioana (Computing and Informatics, 2014)
This paper presents a number of security and VO management capabilities in a large-scale distributed Grid operating system. The capabilities formed the basis of the design and implementation of a number of security and VO management services in the system. The main aim of the paper is to provide some idea of the various functionality cases that need to be considered when designing similar large-scale systems in the future.